PENGARUH PELATIHAN DAN PENGEMBANGAN KARIER TERHADAP KINERJA KARYAWAN PERUSAHAAN KORPORASI - Jumawan, Jumawan; Mora, Martin Tanjung (Jurnal Riset Manajemen dan Bisnis (JRMB) Fakultas Ekonomi UNIAT, 2018)
This research aims to review and analyze the influence of training and development of the performance of employees. The population in this research is of permanent workers at the PT. Nawakara Mighty Nusantara, which consisted of 72 people. Researchers used saturated where sample of a whole population are only sampled. The method of analysis of the data used in this research was the worship of idols linear regression analysis. The research results show that a ) training in full have had a positive impact and significant on the performance of employees, b ) the development of a career in full have had a positive impact and significant on the performance of employees, c ) training and the development of a career together significant impact on employee performance. And d ) a variable that dominant that influences the performance employees is the development of a career. Keywords: training, the development of career, and performance employees.